KUZGI BUG‘DOYNING UNIB CHIQISH JADALLIGIGA TABIIY ADSORBENTLARNI QO‘LLASHNING AHAMIYATI (AGROINNOVATSIYА, 2024)
This article presents data on the effect of natural adsorbents on autumn wheat at different rates on the germination rate of autumn wheat.